Aplikasi Mobile Pencarian Lokasi Praktik Dokter Gigi di Wilayah Medan Marelan Menggunakan Location Based Service (LBS) dan Metode Euclidean Distance - Muhammad Rizky Alfama; Efani Desi (Yayasan Kawanad, 2026)
The lack of digital information regarding the distribution of medical personnel, particularly dentists, in the Medan Marelan subdistrict often makes it difficult for the community to access prompt medical care. To address this issue, this study developed a mobile application for Android devices capable of providing accurate information on the locations of dental practices. The application uses Location-Based Service (LBS) technology and the Euclidean Distance algorithm to determine the user's location and calculate the shortest distance to the nearest dental practice. The software was developed using Android Studio, the Java programming language, and the Google Maps API to create an interactive map. After testing at 10 locations in Medan Marelan, the system successfully determined distances accurately, with the closest distance being 0.008329 degrees. Black-box testing also confirmed that the navigation and search functions operated without technical issues. With this application, it is hoped that the information gap regarding dental healthcare services can be bridged, improving time efficiency for communities in need of dental care.